Development of Recommendations to Continue Anticoagulation with One of the Two Types of Oral Anticoagulants Based on the Identification of Patients' Preference - Zolfaghari, Shabnam; Harenberg, Job; Frölich, Lutz; Weiss, Christel; Wehling, Martin; Wild, Philip; Prochaska, Jürgen; Beyer-Westendorf, Jan; Koscielny, Jürgen; Lip, Gregory Y. H. (Seminars in Thrombosis and Hemostasis, 2015)
Patients with indication for anticoagulation may prefer treatment with a vitamin K antagonist (VKA) or non-vitamin K antagonist oral anticoagulant (NOAC). A questionnaire may help to identify the preference of patients for one of the two types of oral anticoagulants and to develop a score for the recommendation to continue or to change the anticoagulant. A score was developed using a questionnaire containing biographic data and eight statements on attitudes on anticoagulation and was derived to trigger continuation or change the type of anticoagulant by defining ranges of terms and weighting of the significant statements identified by logistic regression analysis. Participating patients received either anticoagulation with VKA (group 1, n = 690), were transferred from VKA to NOAC (group 2, n = 158), received NOAC de novo (group 3, n = 137) or were transferred from NOAC to VKA (group 4, n = 19). Four statements were significantly (p values between 0.0347 and < 0.0001) associated with recommendations to maintain or to change the type of anticoagulant for patients in groups 1, 2, or 3 with predictive values of c = 0.83 between groups 1 and 2 and c = 0.71 between groups 1 and 3. From the total number of replies to the statements a score of three grades and two strengths (A = strong, B = moderate) was derived for the recommendations. This tool supports recommendations as to continue or to change the presently used type of oral anticoagulant based on the identification of patients' preferences.
Keywords: anticoagulation; vitamin K antagonist; new oral anticoagulant; preference; questionnaire; score; recommendation